Are Political and Economic Integration Intertwined? - Bernt Bratsberg; Giovanni Facchini; Tommaso Frattini; Anna Rosso (Institute of Labor Economics (IZA), 2019)
Economic incentives play a key role in the decision to run for office, but little is known on how they shape immigrants' selection into candidacy. We study this question using a two-period Roy model and show that if returns to labour market experience are higher for migrants than natives, migrants will be less likely to seek office than natives. We empirically assess this prediction using administrative data from Norway, a country with a very liberal regime for participation in local elections. Our results strongly support our theoretical model and indicate that immigrants' political and economic integration are closely intertwined.
Keywords: F22; J45; P16; 330; immigration; local elections; candidacy decision; labour markets